Gordon Research Conference on Nuclear Chemistry, 1952 - Gordon Research Conferences (1952)
Group photograph of attendees at the Gordon Research Conference on Nuclear Chemistry held in New Hampton, New Hampshire, June 1952. Included with the photograph are a hand-drawn key and name list identifying the individuals depicted in the photo.
Keywords: Gordon Research Conferences; Portraits, Group; Congresses and conventions